Implementasi Akad Wakalah Bil Ujrah - Vina Agustina; Zumara Zumara (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This article aims to analyze the implementation of the wakalah bil ujrah contract at BSI Subang Otista 2. Wakalah contract is a contract found in the world of Islamic banking. Wakalah bil ujrah is to represent or refer another person to represent him accompanied by a reward that has been mentioned at the beginning. This writing uses qualitative research methods, data sources are taken from primary data sources which conduct interviews supported by literature, the type of data is qualitative data, data collection techniques are carried out by semi-structured interviews which in their implementation are more open as well as in finding more open problems supported by tracking literature related to wakalah bil ujrah, data analysis techniques in the form of descriptive analysis techniques. Based on the research conducted, the implementation of the application of the wakalah bil ujrah contract at BSI Subang Otista 2 such as for the purchase of goods such as houses, building materials, vehicle purchases, all the goods are clear and usually there is a wakalah contract first and then murobahahah with the bank. Wakalah bil ujrah is used in Islamic banking because sometimes the goods that customers want are certain goods. The determination of ujrah or reward is determined at the beginning of the contract.